Analisis Cara Penanganan Penurunan Kualitas Batubara di Stock ROM Ulak Pandan Sampai Jetty SDJ di PT Bumi Merapi Energy - Hajiardi, Dovi; Husni, Ahmad; Susilo, Aris (Green Publisher Indonesia, 2024)
Coal quality analysis is increasingly important considering the increasing global energy demand. Coal, as the main source of energy, has varying qualities, affecting combustion efficiency and environmental impact. Two commonly used analysis methods are proximate analysis and ultimate analysis, which provide information about the composition of coal. Previous research has shown that chemical analysis affects energy efficiency and environmental impact. This study aims to analyze the quality of coal using both methods and evaluate its characteristics for industrial applications. The benefits of this research include guidance for coal producers and users, as well as contributions to reducing the environmental impact and sustainability of the energy sector. This study uses a descriptive approach with qualitative and quantitative methods, focusing on Seam E coal at PT Bukit Asam Tbk. Primary data includes coal handling, temperature, and quality, while secondary data includes location maps and rainfall data as a reference. This study resulted in the conclusion that 1) Factors that affect the decline in coal quality at mining sites and stockpiles include the mining process, working front conditions, loading, processing in the stockpile, sampling, and handling in the ROM to Jetty SDJ. 2) Efforts made include contamination avoidance, fine coal handling, stacking management, and blending process.